Social Capital”“Based Edupreneurship in Arabic Language Education: A Case Study of SmartKids Tutoring Center in Kedungringin Village - A'yun, Siska Qurrota; Rohmah, Lailatu; Shodiq, Muhammad Jafar; Azzahra, Talitha Rahma; Fitri Aeni, Azizah Nur (Universitas Muhammadiyah Magelang, 2025)
Edupreneurship has emerged as an alternative approach to sustaining educational services, particularly in non-formal learning contexts. This study aims to analyze the implementation of social capital”“based edupreneurship in Arabic language education at the SmartKids tutoring center in Kedungringin Village. Employing a qualitative case study design, data were collected through in-depth interviews, participant observations, and documentation. The data were analyzed using thematic analysis to identify key patterns in the utilization of social capital. The findings reveal that SmartKids Bimbel successfully integrates social capital into its educational practices through three main forms: bonding social capital among tutors and learners, bridging social capital through collaboration with parents and community members, and linking social capital through engagement with local institutions. These forms of social capital contribute to the sustainability of Arabic language learning programs, strengthen community trust, and enhance learners”™ motivation and participation. The study highlights that social capital”“based edupreneurship can serve as an effective model for developing community-oriented Arabic language education in non-formal settings. The findings provide practical implications for educators and educational entrepreneurs seeking to integrate social capital into innovative and sustainable educational practices.